(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1912)
A description of seventeen newly discovered cross-slabs is provided. There are seven with incised linear crosses and seven with incised outline crosses. A broken slab from the parish of Bride, has on one face a carefully chiselled Celtic cross, the limbs connected by a circular ring, and the whole contained within a rectangular panel. It is inscribed by what look like Latinised forms of Celtic men’s names. A single piece is of much later date and Scandinavian in character, and dating probably from the twelfth century.